Flood water level detection for student notification - Nur Izzah Nadhirah, Abdul Majid (2018)
Flood Water Level Detection for Student Notification is the one of the system that be created to help people especially UMP Students who is lived in flooding area. The road user especially UMP student and staff usually get late information about the road situation that they want to use and sometime they will be stuck and need to turn back and used another road. This objective of this system is to propose new method to collect the data and develop web mobile application and water level monitoring system to acknowledge and record the water level by using Arduino Uno and sensor system. By using the Rapid Application Development (RAD) this system will be produce a suitable software plan with the system that have four phases. This project can help people to manage their way and avoid them from dangerous situation by find another way out. Not only that, it can give more fast information about the flooding area situation. I hope this system will help people to get information and be one of the alternative way to avoided from flood situation or area.